Comparison of Efficacy of FESS (Functional Endoscopic Sinus Surgery) Versus Conventional Intranasal Polypectomy in Patients with Nasal Polyposis - Syed Jawad Hussain Shah , Maisam Ali , Syed Ali Naqi (Journal of Rawalpindi Medical College, 2018)
Background : To Compare the efficacy of Functional Endoscopic Sinus Surgery (FESS) with Conventional Intranasal Polypectomy in patients with nasal polyposis Methods: In this comparative study patients with sino-polyposis were divided into two groups Group-A was allotted to FESS and Group-B to the patients with conventional endoscopic endonasal-polypectomy. All patients,after surgery,were followed till 4 months for efficacy. Frequencies and percentages were calculated for qualitative variable i.e. gender and efficacy. Chi square test was applied to compare the significant difference regarding efficacy of both groups. p-value of ≤0.05 was considered statistically significant. Stratification was done for age and gender of the patients and duration of the disease to control the effect modifiers. Post stratification chi-square test was applied. Results: In group A, the efficacy was found n 82.67% whereas in group B the efficacy was observed in 61.33%. By using chi-square test, the significant association was found between study group and efficacy having p- value = 0.004. Conclusion: Efficacy was significantly higher in the FESS group as compared to conventional intranasal polypectomy in patients with sinonasal polyposis.